The transformation of Tuban Batik colors: perception and value in modern society - Fajar Ciptandi; Morinta Rosandini; Ulfah Nafi’ah (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2023)
This article discusses the philosophical meanings represented by the dominant color in the background of traditional batik cloth in Tuban, East Java, Indonesia. These meanings have provided values and appreciation for the people of Tuban throughout their lives, reflecting a way of life connected to the concept of cosmology from birth to death. However, the current wave of development trends and modernity has impacted how the people of Tuban attribute value and adhere to these philosophical meanings within batik. This research employs an ethnographic approach involving direct data collection at the research location. We immersed ourselves in the local community, engaging in random interactions to gain insight into their thoughts and behaviors. Additionally, to uncover hidden philosophical values, data was collected through oral traditions involving one community leader, two entrepreneurs, and batik craftsmen knowledgeable about these values due to hereditary teachings. Subsequently, the data was analyzed using a phenomenological approach to elucidate the relationship between the philosophical meanings inherent in the traditional Tuban batik color and the daily behavioral patterns of the current population. This exploration illustrates the enduring significance of these philosophical meanings to the Tuban people. These meanings serve as a foundation for contemplating actions that preserve the tradition's continuity in the face of evolving innovations. It is imperative to assess how these values within the tradition are treated—whether maintenance, development, or elimination is appropriate—based on contemporary conditions.